Availability of Next Generation Science Standards in The Field of Earth and Space Sciences: Case of Egypt Middle Schools Science Books - Amany Elgendy; Rafeek Elmeanawy; Wafaa El- Zontahy (International Journal of Instructional Technology and Educational Studies)
The current study aimed to determine the extent to which science standards for the next generation in the field of Earth and space sciences - goals, content, activities, evaluation methods - are included in the preparatory science curricula. The descriptive-analytical method was followed to answer the study questions. An analysis tool was designed, including the three main criteria "Crosscutting concepts, Core ideas, and Scientific and Engineering practices" and their sub-indicators, about general objectives, activities, content, and evaluation. The analysis tool was applied to the field of Earth and space sciences in middle school science books applied in the year 2020-2021. The results of the study revealed that the levels of inclusion were as follows: Teaching and learning activities ranked first with a rate of 64.5%. The content came in second place with 62.2 %. Evaluation methods came in third place 40.8 %. The general goals came in fourth place with a very low percentage of 30.43%. Hence, we find that the field of Earth and space sciences in the preparatory stage, in general, does not sufficiently include the science standards for the next generation. The results also showed that the availability of the three main dimensions (Crosscutting concepts, core ideas, and scientific and engineering practices) was uneven. The Crosscutting concepts ranked first with 65%. Scientific and engineering practices ranked second with 52.3%. The core ideas ranked third with 28.5%.